2022
DOI: 10.3390/su14031830
|View full text |Cite
|
Sign up to set email alerts
|

GIS and AHP Based Groundwater Potential Zones Delineation in Chennai River Basin (CRB), India

Abstract: Groundwater depletion is one of the most critical concerns for users and policymakers. Identifying groundwater potential (low to high) helps properly plan the available groundwater resource. This study has used the possibilities of a geographical information system (GIS), remote sensing and, of course, field data to delineate the groundwater potential zones in the Chennai River Basin (CRB). Thematic layers generated for eleven controlling factors, such as geology, water level, drainage, soil, lineament, rainfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 55 publications
(58 reference statements)
0
20
0
Order By: Relevance
“…These layers were weighted, normalized, and assigned features based on local field experience, professional judgment, and Saaty's AHP. 9,10,14,37 The study obtained a CR value of 0.09, which is acceptable to continue the AHP-based potential mapping analysis. The study revealed that the northern side of the district, which includes high-elevation ranges and river valleys, has a high concentration of poor and very poor (18.804%) potential areas.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These layers were weighted, normalized, and assigned features based on local field experience, professional judgment, and Saaty's AHP. 9,10,14,37 The study obtained a CR value of 0.09, which is acceptable to continue the AHP-based potential mapping analysis. The study revealed that the northern side of the district, which includes high-elevation ranges and river valleys, has a high concentration of poor and very poor (18.804%) potential areas.…”
Section: Discussionmentioning
confidence: 74%
“…36 . The accuracy of the final potential map was verified using groundwater level data, 23 borehole-yield data, 9,10,28 groundwater well locations, 6 the specific capacity of wells, 37 and spring location data. 5 In the present study, eight thematic layers were used in the Papum Pare district, i.e., lithology, soil texture, geomorphology, rainfall, lineament density, slope, drainage density, and spring proximity map.…”
Section: Discussionmentioning
confidence: 99%
“…Land use practices have an impact on the timing, volume, and quality of groundwater recharge, as well as in uencing runoff and evapotranspiration (Rather et al 2022). Regions covered with forests possess a greater potential for groundwater recharge, whereas areas with concrete structures have less capacity for recharge (Sajil Kumar et al 2022). In this study (Fig.…”
Section: Creation Of Thematic Mapsmentioning
confidence: 65%
“…The slope is a signi cant geomorphological characteristic that in uences the potential of groundwater in an area. It is a crucial parameter in assessing the possibilities for groundwater recharge (Sajil Kumar et al 2022). In places where the slope is low, excessive seepage occurs due to the accumulation of surface water.…”
Section: Slopementioning
confidence: 99%
“…Analytic Hierarchy Process (AHP) was proposed by [25] to solve complex decision-making through pairwise comparisons. AHP is a useful method for prospecting groundwater potential zones (GWPZs) [8,26]. For example, ref.…”
Section: Introductionmentioning
confidence: 99%